2016
DOI: 10.22342/jims.22.1.212.37-59
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamical System Approach in Modeling Technology Transfer

Abstract: Abstract. In this paper we discuss a mathematical model of two parties technology transfer from a leader to a follower. The model is reconstructed via dynamical system approach from a known standard Raz and Assa model and we found some important conclusion which have not been discussed in the original model. The model assumes that in the absence of technology transfer from a leader to a follower, both the leader and the follower have a capability to grow independently with a known upper limit of the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In addition to the mentioned issues, several other ecological factors deserve consideration in developing realistic models. These factors include (i) source and sink subpopulation [7,8], (ii) different levels of intraspecific competition [57,58], and (iii) coupled growth function [59]. These elements play a critical role in determining optimal harvesting strategies and the choice between MSY or Quasi MSY as harvesting strategies, as shown in [60].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the mentioned issues, several other ecological factors deserve consideration in developing realistic models. These factors include (i) source and sink subpopulation [7,8], (ii) different levels of intraspecific competition [57,58], and (iii) coupled growth function [59]. These elements play a critical role in determining optimal harvesting strategies and the choice between MSY or Quasi MSY as harvesting strategies, as shown in [60].…”
Section: Discussionmentioning
confidence: 99%
“…The results above are deduced from the specific assumptions used in the construction of the model. It would be interesting to explore the robustness of the results for other ecological issues that are worthy to be taken into account in developing a more realistic model, such as different levels of intraspecific competition [28], the Allee effect [29,30], fear effect [31,32], and a coupled growth function caused by a metapopulation structure [33], which may alter the result in this study. These are being investigated by the authors.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…It is also often some interesting mathematical structures appear in such problems [12,13]. The example of the appearence of eigen value in industrial engineering can be found in [14,15]. Other examples of applications are abound, such as in spectral clustering analysis [16], singular value decomposition for image compression [17], incremental principal component analysis [18], the Google Page Rank algorithm [19].…”
Section: Introductionmentioning
confidence: 99%